P(NMe₂)₃-Mediated Domino Cyclization/Functionalization of Dicyanoalkenes - Xiang, Min; Min, Jia-Xi; Wang, Guang-Wei; Jia, yunqing; Shen, Li-Wen (Synlett)
A P(NMe₂)₃-mediated domino reaction between dicyanoalkenes and benzoylformates has been developed. By switching between isatin-and tetralone-derived dicyanoalkenes, the protocol divergently furnishes either spiro-cyclopropyl oxindoles or α-functionalized dicyanoalkenes in up to 99 % yield under mild conditions. Gram-scale experiments and broad substrate scope highlight the synthetic utility of the transformation.